2006
DOI: 10.1021/om0603114
|View full text |Cite
|
Sign up to set email alerts
|

The First Carbene Complex of a Diorganoberyllium:  Synthesis and Structural Characterization of Ph2Be(i-Pr-carbene) and Ph2Be(n-Bu2O)

Abstract: The reaction of base-free Ph 2 Be with 1, in toluene gaVe the carbene adduct Ph 2 Be(i-Pr-carbene) (1) as colorless crystal blocks. For comparison, the di-n-butyl ether adduct Ph 2 -Be(n-Bu 2 O) (2) was prepared from BeCl 2 and PhLi in a mixture of Et 2 O and n-Bu 2 O. Single-crystal X-ray determinations reVeal monomeric solid-state structures for both complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
66
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 17 publications
15
66
0
2
Order By: Relevance
“…This procedure resulted after work-up in the isolation of compound 1 ([BeMe 2 (IPr)]) as a colorless microcrystalline material in 56 % yield. Like the previously reported [BePh 2 (iPr-carbene)] (iPr-carbene = 1,3-diisopropyl-4,5-dimethylimidazol-2-ylidene), [8] compound 1 was shown to maintain its three-coordinate geometry; in the solid state by an X-ray diffraction analysis and in solution through a combination of 1 H, 13 C, 9 Be, and diffusion (DOSY) NMR spectroscopic techniques (see the Supporting Information).…”
supporting
confidence: 63%
See 1 more Smart Citation
“…This procedure resulted after work-up in the isolation of compound 1 ([BeMe 2 (IPr)]) as a colorless microcrystalline material in 56 % yield. Like the previously reported [BePh 2 (iPr-carbene)] (iPr-carbene = 1,3-diisopropyl-4,5-dimethylimidazol-2-ylidene), [8] compound 1 was shown to maintain its three-coordinate geometry; in the solid state by an X-ray diffraction analysis and in solution through a combination of 1 H, 13 C, 9 Be, and diffusion (DOSY) NMR spectroscopic techniques (see the Supporting Information).…”
supporting
confidence: 63%
“…It may also be noted that the amidoalkylberyllium component of 3 is isomeric to the target IPr adduct of BeH 2 , which then requires the presence of free IPr to crystallize. This scenario also requires the production of half a molar equivalent of the initial beryllium added as compound 2 to be present as an as yet unidentified beryllium species, possibly THF-solvated BeH 2 , a supposition that is reinforced by the observation of an additional resonance in the 9 Be{ 1 H} NMR spectrum at d = 0.65 ppm alongside the signal attributed to compound 3 at d = 16.9 ppm.…”
mentioning
confidence: 99%
“…[64] However,despite several attempts,a ll complexes that has been prepared feature aB ei nt he oxidation state + 2. [65] The superiority of CAACst oa ccess Be 0 complexes is due to their stronger p-accepting properties.Note that theoretical studies predict that Mg 0 complexes are synthetically unviable [64a] with classical ligands (CO,PR 3 ,NHC);however it remains to be shown that CAACs cannot do it.…”
Section: Caacs In Group 1a Nd Group 2element Chemistrymentioning
confidence: 99%
“…[13,22,24,26,27] (7), [13] or diarylberyllium (8)c ompounds. [26] Accordingly,a lso lithium phenolates can be reacted with BeCl 2 in diethyle ther to beryllium phenolates (9). [24] In all three cases the beryllium atom is threefold coordinatedw ith an ether serving as the third ligand.…”
Section: O-donorligandsmentioning
confidence: 99%